Engaging patients in stroke rehabilitation unit: an approach in patient centered care - Ekawati, Dessy Natalia; Utami, Yulian Wiji; Fevriasanty, Fransiska Imavike (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2025)
Background: Engagement and collaboration between healthcare providers and patients are pivotal in driving patient-centered care, particularly stroke care. A comprehensive and holistic approach to treating stroke patients necessitates the active involvement of caregivers and patients in the decision-making process.Objectives: This study set out to conduct a comprehensive literature review focusing on patient engagement and participatory approaches within the Stroke unitMethods: A scoping review was conducted by compiling scholarly articles from ScienceDirect, PubMed, and ProQuest from 2020 to 2024. Specific keywords, including Patient Engagement, Early Mobilization, and Stroke, were utilized. Adhering to the PRISMA method and pre-established inclusion and exclusion criteria, initially, 540 research articles were retrieved, ultimately undergoing analysis of 15 articlesResults: The findings underscore the importance of holistic and participatory approaches, the engagement of patients and practitioners, the development and integration of therapy and rehabilitation programs, self-management, early mobilization, and efficient communication. Engagement between patients and healthcare professionals is of paramount importance. Practitioners' active participation significantly enhances patient involvement. Trust is particularly crucial for individuals who have experienced a stroke, as it profoundly influences their decision-making processes. Emphasizing health literacy and promoting shared decision-making can improve communication and patient involvement, even when facing time constraints.Conclusions: In conclusion, the active involvement of patients and participative action of practitioners across various facets of therapy and rehabilitation augments program effectiveness and positively influences the quality of life for post-stroke patients. Enhancing stroke survivors' outcomes through self-management and early movement initiatives is particularly beneficial for individuals experiencing communication difficulties. This approach necessitates a coordinated team effort and ongoing support throughout the rehabilitation process.